Dynamics of Livestock Market in Rural Indonesia: A Case Study of Traditional Cattle Trading at Solok District, West Sumatera - Madarisa, Fuad; Edwin, Tevina; Rahmadhani, Sri Putri (Andalasian Livestock, 2025)
This study examined the dynamics of the traditional cattle trading in Solok Regency, West Sumatra, Indonesia, focusing on the Muaro Paneh livestock market. Livestock markets support rural economies by facilitating animal transactions, disseminating market information, preserving cultural practices, and maintaining social networks. Despite the significance of this market, there was a lack of research on micro-level rural livestock markets in Indonesia. This study aimed to fill the gap by investigating the structure, key actors, and transactional mechanisms of the traditional cattle trade in Solok District. Using a qualitative case study approach, the research exposed the underlying dynamics of rural livestock markets, evaluate their resilience, and provide empirical insights for inclusive and context-sensitive livestock development policies. The findings emphasize the importance of traditional livestock markets in rural transformation and sustainable livestock systems.